2015
DOI: 10.1371/journal.pone.0124934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Income Inequality and Other Social Determinants on Suicide Rate in Brazil

Abstract: Studies about suicide worldwide have mainly focused on individual-level psychiatric risk factors. In Brazil, suicide is an important public health problem. Brazil has evidenced important socioeconomic changes over the last decades, leading to decreasing income inequality. However, the impact of income inequality on suicide rate has never been studied in the country.PurposeTo analyze whether income inequality and other social determinants are associated with suicide rate in Brazil.MethodThis study used panel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 30 publications
2
71
0
19
Order By: Relevance
“…Individual factors that affect the risk of suicide include mental disorders, genetics, drug misuse, psychological states and cultural, family and social situations, and some of these frequently coexist. [5][6][7] A correlation between suicidal intent and lethality has also been reported in the literature. 19 Socioeconomic problems such as unemployment, poverty, homelessness and discrimination may also trigger suicidal behavior.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Individual factors that affect the risk of suicide include mental disorders, genetics, drug misuse, psychological states and cultural, family and social situations, and some of these frequently coexist. [5][6][7] A correlation between suicidal intent and lethality has also been reported in the literature. 19 Socioeconomic problems such as unemployment, poverty, homelessness and discrimination may also trigger suicidal behavior.…”
Section: Discussionmentioning
confidence: 91%
“…However, Machado et al 6 and Kim 28 concluded that inequality is an important determinant of suicide, both in Brazil and in the US.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O estudo dessa questão e suas associações é importante, pois sua ocorrência teve aumento global nas últi mas décadas 2 , e no Brasil, entre 1996 e 2010, houve um aumento de 6,4 vezes por 100 mil habitantes 3 . A cidade de Barra do Garças (MT) acompanha o país nessa epidemiologia, sendo a única cidade do Mato Grosso que possui trabalhos estatí sti cos sobre o tema, com análises sobre prevalência e incidência nos diversos grupos sociais 4 .…”
Section: Introductionunclassified